HANDLING OF FOREIGN REFUGEES IN PANDEMIC TIMES IN CRIMINOLOGICAL THEORY PERSPECTIVE (CASE STUDY OF THE ENVIRONMENT OF SIRIH GARDEN, JAKARTA - Fachrizza Sidi Pratama; Hana Farah Dhiba; Rafsanjani Ismarus (Polteknik Imigrasi, 2021)
In Indonesia, more than 13,645 confirmed cases and the death toll reached 959 victims. In suppressing the number of spreads, the government has issued various policies with WHO standards, one of which is large-scale social restrictions (PSBB) by limiting community activities and movements as an effort to quarantine a region's health while still mobilizing basic needs for Indonesian citizens (WNI) and other citizens. affected foreigners. In the midst of the condition of the spread of the Covid-19 virus, which does not look at who will be infected, there is a group of people who have been neglected and have not been touched by much assistance from the government. They are refugees and asylum seekers residing in Indonesian territory. Being a complex problem, in the absence of domestic laws that regulate the problem of handling refugees, as well as the condition of refugees who have a high level of infection with Covid-19, this causes an anomaly in the enforcement of human rights (HAM). The Indonesian government in handling the Covid-19 pandemic should ensure that all levels of society are made a top priority, including refugees. The provision of access to social assistance is also considered, such as the provision of adequate shelter rooms, food supplies, personal protective health equipment (masks, antiseptics), as well as medical services and facilities.